Geographic Distribution and Population Estimate of Leaf-cutting Ants of the Genus Acromyrmex (Hymenoptera: Formicidae) in Southwestern Bahia - Santos, Vanessa Correa; Melo, Thiagi Lima; Vaz, Aline Brito; Moreira, Aldenise Alves; Castellani, Maria Aparecida; Protti de Andrade, Ana Paula; Forti, Luiz Carlos [UNESP]; Santos de Lemos, Raimunda Nonata; Vaz, Aline Brito (California State University, 2010)
The objectives of this study were to develop knowledge about the diversity of leaf-cutting ants of the genus Acromyrmex in Southwestern Bahia, Brazil, relate their occurrence to the predominant vegetation and estimate their population size. The survey was undertaken in 36 municipalities, with demarcation and georeferencing of collection points and observation of the predominant vegetation. Collections were performed along the road sides, in a 1,600 km long area. Sample collection points were established at every 50 km, and ants were collected within a distance of 50 m from each side of the road. Collected material was fixed in 70% ethanol for later identification at the species level at the Laboratory of Social-Pest Insects of the São Paulo State University (UNESP), Botucatu campus, São Paulo. Excavations were conducted in 12 active nests of Acromyrmex balzani with the aim of collecting colonies for estimates of population size. The following species were found: Acromyrmex landolti, A. balzani, A. rugosus rugosus, and A. lobicornis. The most frequent species were A. landolti and A. balzani. There were no great vegetation differences in the sampled areas, which made it difficult to identify the best bioecological interactions. In the excavated nests of A. balzani, the number of workers ranged from 102 to 700 individuals.
Keywords: diversity; Formicidae; leaf-cutting ants